IMPLEMENTASI MEDIA FLASHCARD DALAM MENGEMBANGKAN KEMAMPUAN BAHASA ANAK USIA DINI DI TK TUNAS INSAN KAMIL 01 SERANG - Siti Dewi Winengsih; Tri Sayekti; Isti Rusdiyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of flashcards in improving the language skills of early childhood students at Tunas Insan Kamil 01 Serang Kindergarten. Flashcards are used as a learning tool because they are visual, attractive, and suitable for early childhood characteristics. This study uses a qualitative approach with a descriptive method. The research subjects are teachers and children in group B2 at Tunas Insan Kamil 01 Serang Kindergarten. Data collection was carried out through observation, interviews, and documentation, while data analysis included data reduction, data presentation, and conclusion drawing. The results showed that the planned and structured use of flashcards improved children's language skills, particularly in the area of expressive language, such as vocabulary mastery, pronunciation, and confidence in speaking. Learning became more enjoyable and encouraged children to participate actively. Supporting factors included the availability of media and the active role of teachers, while obstacles included time constraints and differences in children's language abilities.